Biogas upgrading by adsorption onto activated carbon and carbon molecular sieves: Experimental and modelling study in binary CO2/CH4 mixture. Issue 5 (October 2021) - Rainone, Fabrizio; D'Agostino, Ottavia; Erto, Alessandro; Balsamo, Marco; Lancia, Amedeo
Abstract: Biomethane, a renewable form of natural gas, can be produced by biogas upgrading and its utilization is incentivized to mitigate CO2 emissions. In this work, biogas upgrading via adsorption on commercial carbonaceous adsorbents, an activated carbon (AC) provided by Desotec and two carbon molecular sieves (CMSs) produced by Carbotech and Xintao, is experimentally investigated in a fixed-bed column, testing CO2 /CH4 mixtures at different concentrations as feed gas. The experimental campaign highlights that AC has a higher adsorption capacity for both CO2 and CH4, as well as better kinetic performances (i.e. higher bed usage efficiency and lower desorption times), than CMSs. On the other hand, the CMSs show a much lower CH4 adsorption capacity than the AC due to their combined thermodynamic/kinetic sieving properties, which emerge from dynamic breakthrough curves and equilibrium adsorption data alike. Therefore, the CMSs show a much higher selectivity for the separation of the CO2 /CH4 mixture, and Xintao sample shows a better overall performance thanks to its faster kinetics; moreover, experimental cyclic adsorption/desorption runs on Xintao confirmed its complete regenerability. Breakthrough curves modelling, performed in MATLAB environment and aimed at evaluating the CO2 mass transfer coefficients, points out that intraparticle diffusion is the rate-limiting step for CO2 adsorption process. It can be concluded that CMSs show better performances for biogas upgrading due to their high selectivity and despite their lower CO2 adsorption capacity, which cannot be taken as the main controlling parameter in the adsorbent selection devoted to this specific application. Graphical Abstract: ga1 Highlights: Carbon molecular sieves outperform activated carbon for CO2 /CH4 separation. Equilibrium/kinetic sieving effects emerge from breakthrough and equilibrium data. Intraparticle diffusion is the rate-limiting step for the adsorption process. Constant CO2 adsorption capacity for cyclic reuse and desorption at 80 °C. Selectivity and kinetics are the leading parameters for an optimal adsorbent choice.